2009
DOI: 10.1002/sia.3129
|View full text |Cite
|
Sign up to set email alerts
|

18O/16O isotopic separation in anodic tantala films by glow discharge time‐of‐flight mass spectrometry

Abstract: Glow discharge mass spectrometry has been widely used for trace and ultra-trace element analysis of high-purity alloys. A novel pulsed radio frequency glow discharge time-of-flight mass spectrometer (rf GD TOFMS) has been developed that retains the pulsed radio frequency analytical ion source to provide ion signal enhancement due to processes involving Penning ionisation. A time-resolved detection mode has been implemented to sample the afterglow regime of the pulse profile, corresponding to the highest ion si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
0
10
1
Order By: Relevance
“…Recently, the analytical capabilities of rf-PGD-ToFMS have been successfully investigated for depth profile analysis of nanostructured materials, 12 polymers, 13 implanted silicon 14 and anodic tantala films. 15 It is well known that the hydrogen content on high quality intrinsic and doped a-Si:H thin films is around 10%. 4 It has been previously reported that the addition of hydrogen to Ar GD seriously affects the intensity of the analytes and reduces the sputtering rate.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the analytical capabilities of rf-PGD-ToFMS have been successfully investigated for depth profile analysis of nanostructured materials, 12 polymers, 13 implanted silicon 14 and anodic tantala films. 15 It is well known that the hydrogen content on high quality intrinsic and doped a-Si:H thin films is around 10%. 4 It has been previously reported that the addition of hydrogen to Ar GD seriously affects the intensity of the analytes and reduces the sputtering rate.…”
Section: Introductionmentioning
confidence: 99%
“…An ideal material for testing and evaluation is anodic tantala [17]. Anodic tantala films may be formed in a very wide range of electrolytes, allowing incorporation of appropriate species.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Secondary-ion mass spectrometry and time of flight glow discharge mass spectrometry may also be employed with sputtering of the oxide layers or imaging of oxide cross sections. [10][11][12][13][14][15][16] In the present work, 18 O tracer is used with NRA to investigate the formation of porous films on aluminum under mild anodizing conditions. Porous anodic films have been studied extensively due to their importance in the protection of aluminum alloys 17 and, more recently, for various nanotechnological applications.…”
mentioning
confidence: 99%